Analisis Kemampuan Berpikir Kritis Pada Mata Pelajaran Matematika: Studi Pembelajaran Menggunakan Model Problem Based Learning (PBL) - Nurfitriyani; Muhammad Makki; Husniati (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
Critical This research is motivated by students' critical thinking skills which are still relatively low. This study aims to determine the effect of the problem based learning model on students' critical thinking skills in the fourth grade mathematics learning content at SDN 38 Mataram. This type of research is experimental research with Pre-experimental design type Preetest-Postest One-Group Design. The population of this study were students of class IV-A SDN 38 Mataram with a total of 20 students consisting of 8 boys and 12 girls. The sampling technique used a saturated sample technique with a class IV-A sample of SDN 38 Mataram. The data collection technique in this research is in the form of a description test that refers to indicators of critical thinking skills. Data analysis was carried out by homogeneity test which obtained a Sig value of 0.221 indicating that class VI-A data was homogeneous and normality test data obtained a Sig value of 0.120 which indicated that the data were normally distributed. While the hypothesis test using the Paired sample t-test formula by obtaining a Sig (2-tailed) value of 0.000, this is smaller than the value of 0.05. So it can be concluded that there is an effect of the problem based learning model on students' critical thinking skills in the fourth grade mathematics learning content at SDN 38 Mataram. Thus the problem-based learning model can be applied to fourth grade elementary school students to determine students' critical thinking skills in learning mathematics.